Development and Validation Trials of User-friendly Disinfectant for Containment of Tasar Silkworm Diseases - Kumar, K.P. Kiran; Sinha, A.K.; Singh, G.P.; Sharma, S.P.; Rai, Suresh; Sahay, Alok (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
As there are no curative measures for the control of silkworm diseases, different preventive methods using formaldehyde or chlorine based chemical disinfectants are being practiced in tasar culture. But these disinfectants are hazardous to the users and environment. Moreover, these chemicals have limitations to be effective in open field. Hence, the project was taken up to developed user friendly disinfectant suitable to the open field rearing conditions of the tasar culture. Based on the in vitro inactivation studies of the previous experiment the best performed user friendly chemicals namely Tri-sodium orthophosphate (TSP), Slaked lime (SL), Urea (UR) and Desnet (DN) were selected, prepared certain combinations and conducted in vivo studies. The best performed user friendly disinfectant was subjected to on form trials in CTR&TI field and validation trials in different states of RTRSs and results were statistically evaluated. In vivo studies of user friendly disinfectant (TSP+ SL+UR) have shown less mortality due to the various diseases than any other treatments and mortality percentage recorded was below 6% in case of all tested pathogens. Another combination, DN + SL+ UR occupied last passion with disappointed results which even did not cross the values of the control. In inoculated control mortality percentage was ranged from 53% to 98.83% which directly indicated effect of the pathogens on the cocoon yield. On form trials of user friendly disinfectant results revealed that, Cocoon yield/Dfl ranged from 40.00 to 123 cocoons/Dfl with the average of 74.40 cocoons/Dfl. and values recorded for S.D and C.V% were 34.81 cocoons and 46.79% respectively in treated lots where as in control, Cocoon yield/Dfl ranged from 30.50 to 101 cocoons/Dfl with the average of 59.40 cocoons/Dfl and values recorded for S.D and C.V% are 29.77 cocoons and 50.12%, respectively. In treated lots, Single cocoon weight, Single shell weight and S.R% slightly improved over the control. RTRSs of Jagadalpur, Bhandara and Warangal conducted validation trials of user friendly disinfectant and results revealed that, Cocoon yield/ Dfl, Single cocoon weight, Single shell weight and S.R% were increased in user-friendly disinfectant lots when compared with control. Data of on form trials and validation trials were pooled and the improvement was caluculated, 13.99 cocoons/Dfl in the yield, 0.30g in Single cocoon weight, 0.07g in Single shell weight and 0.26% in Shell ratio improvement in treated lots, over the control was observed. T-test analysis of pooled data indicated that the mean value of treated lot Cocoon Yield/Dfl is more than control which is significantly different at 5% level, at the same time mean values of treated lots Single cocoon weight, Single shell weight and S.R% are more than control but not significantly different. Newly developed disinfectant is user friendly and acts against all kinds of disease causing pathogens of tasar silkworm. The developed user friendly disinfectant can be useful to the tasar farmers to obtain stable and improved cocoon yield by suppressing diseases.